ASPEK TUTUR DALAM GEGURITAN LODHA - Giri Pratama, I Gede Angga (Humanis; Volume 5. No. 3. Desember 2013)
Geguritan Lodha is a kind of tutur that is packaged in the form of geguritan. This study will reveal aspects of the tutur that contained therein. This research through several stages, namely: (1) stage providing data using observational methods aided with technical reading, recording, and translation; (2) stage of data analysis using qualitative methods and descriptive analytic techniques aided; (3) stage presentation of the analysis results using formal methods and informal as well as assisted with the deductive and inductive intellection. As for some aspects of the tutur contained in Geguritan Lodha interpreted with some literature that relating to the terms mentioned in Geguritan Lodha then described by ordinary words. Aspects of the tutur that contained has explain the process of creation and find a way later to the freedom (moksha).
Keywords: geguritan, aspects, tutur